Synthesis of chalcone incorporated quinazoline derivatives as anticancer agents - Sapavat Madhavi; Reddymasu Sreenivasulu; Jyothsna Pragathi Yazala; Rudraraju Ramesh Raju (Elsevier, 2017)
A series of ten novel chalcone incorporated quinazoline derivatives (11a-11j) were designed and synthesized. All the synthesized compounds were evaluated for their anticancer activities against four human cancer cell lines (A549, HT-29, MCF-7 and A375). Among them, four compounds, 11f, 11g, 11i and 11j showed more potent anticancer activity than the control drug, Combretastatin - A4.